Diagnosing human cutaneous leishmaniasis using fluorescence in situ hybridization - Kaluarachchi, T. J.; Wickremasinghe, R.; Weerasekera, M.; Yasawardene, S.; McBain, A. J. (PATHOGENS AND GLOBAL HEALTH, 2021)
Cutaneous leishmaniasis (CL) is endemic in Sri Lanka. Giemsa-stained slit-skin-smears (SSSGiemsa) and histology are routinely used in diagnosis with a sensitivity of 40–70%. PCR currently has limited accessibility. Therefore, we assessed the sensitivity and specificity of a previously described fluorescence in situ hybridization assay, on skin smears and biopsy samples to overcome the limitations encountered with routine diagnostic methods. Samples from a total of 123 suspected CL patients were collected and subjected to SSSGiemsa, fluorescence in situ hybridization (FISH) on slit skin smears (SSS-FISH), formalin-fixedparaffin-embedded-tissues stained with Hematoxylin & Eosin staining (FFPE-H&E) and FISH on formalin-fixed-paraffin-embedded-tissues (FFPE-FISH). Negative controls of 61 patient samples were collected from a CL non-endemic area and subjected to the same procedures. The gold standard PCR was used as a comparator. For FISH, two previously described cyanine 3 tagged Leihsmania genus-specific probes were used. Compared to PCR, SSS-Giemsa, SSS-FISH, FFPE-H&E, and FFPE-FISH had sensitivities of 76.5%, 79.1%, 50.4% and 80.9%, respectively. Routine diagnostic tests (SSS-Giemsa and FFPE-H&E) had a specificity of 100%. SSS-FISH and FFPE-FISH had specificities of 96.7% and 93.4%, respectively. FFPE-FISH had a statistically significant higher diagnostic performance than FFPE-H&E (p < 0.001). The relative performance of SSS-Giemsa, SSS-FISH and FFPE-FISH was similar (p > 0.05 for all comparisons). We conclude that FFPE-FISH is a more accurate diagnostic tool than FFPE–H&E. SSS-FISH did not have an additional advantage over SSS-Giemsa in diagnosis. However, SSS-FISH could be recommended as a minimally invasive method in studies assessing wound healing where immunological probes are used.
Keywords: Cutaneous leishmaniasis; fluorescence in situ hybridization; Sri Lanka